Organizational Results of Secondary School Teachers' Formal and Natural Group Relationships in Schools - Gök, Ebru Burcu Çimili (Bartın Üniversitesi, 2022)
The aim of this study is to determine the organizational results of formal and informal group relations of teachers at schools. In accordance with the holistic multiple case pattern, study group of the research has been selected on the basis of volunteerism and maximum diversity sampling out of purpose sampling methods. The group consists of 12 teachers from 3 middle schools Muratpaşa, Kepez and Aksu towns of Antalya province, respectively. Descriptive analysis has been used in the analysis of the qualitative data and consistency testing has been utilized. The Cohen's Kappa reliability coefficient has been calculated as meaningful with the level of 0.818. According to the results of the research; group relations increase organizational commitment and job satisfaction, while reducing stress. In addition, good friendship relationships increase school loyalty and reduce the intention of relocation. However, negative results such as conflicts between different groups have an adverse effect on the organizational climate and the resistance of the members of the group to the decisions of the administration by taking power from each other. Emotional commitment levels of teachers were higher than continuation commitment and normative commitment. Relationships with other employees and perceived social support were mostly affected by job satisfaction. The most stressful resource among the participating teachers is school administrators and it is seen that the participants have been observed emotion-focused coping strategy in the first place.

Bu araştırmanın amacı, öğretmenlerin okullardaki biçimsel ve doğal grup ilişkilerinin örgütsel sonuçlarını belirlemektir. Nitel araştırma desenlerinden durum çalışması ve bütüncül çoklu durum deseni kullanılmıştır. Maksimum çeşitlilik örneklemesi yöntemine ve gönüllülük esasına göre seçilen Antalya ili Muratpaşa, Kepez ve Aksu ilçelerinde bulunan üç ortaokuldaki 12 öğretmenle bireysel ve odak grup görüşmeleri gerçekleştirilmiştir. Nitel verilerin analizinde betimsel analiz kullanılmıştır. Nitel araştırmanın iç güvenirliğini artırmak için tutarlılık incelemesi yönteminden yararlanılmış, Kohen Kappa tutarlılık katsayısı 0.818 düzeyinde anlamlı olarak hesaplanmıştır. Araştırmadan elde edilen sonuçlara göre; grup ilişkileri öğretmenlerde örgütsel bağlılığı ve iş doyumunu artırırken, stresi azaltmaktadır. Ayrıca iyi arkadaşlık ilişkileri okula bağlılığı artırırken, yer değiştirme niyetini azaltmaktadır. Ancak farklı gruplar arası yaşanan çatışmaların kişileri ve örgüt iklimini olumsuz etkilemesi, grup üyelerinin iş yavaşlatan kişilere uyması sonucu işlerin aksaması, grup ya da grupların birbirinden güç alarak yönetimin kararlarına direnç göstermesi gibi olumsuz sonuçlar da ortaya çıkmıştır. Öğretmenlerin duygusal bağlılık düzeyleri, devam bağlılığı ve normatif bağlılıklarına göre daha sık rastlanmıştır. İş doyumunu en çok diğer çalışanlarla ilişkiler ve algılanan sosyal desteğin etkilediği görülmüştür. Çalışmaya katılan öğretmenlerin çoğu stres kaynağı olarak okul yöneticilerini işaret ederken, stresle başa çıkma stratejisi olarak duygu odaklı başa çıkma stratejisini kullandıkları görülmektedir.
Ortaokul Öğretmenlerinin Okullardaki Biçimsel ve Doğal Grup İlişkilerinin Örgütsel Sonuçları
Keywords: Other Fields of Education; Alan Eğitimleri